Konsep Penyalahgunaan Wewenang Dalam Penerbitan Izin Usaha Pertambangan (IUP) Sebagai Tindak Pidana Korupsi - Faiqah Nur Azizah (UIN Syarif Hidayatullah Jakarta, 2022)
Abuse of authority occurs because of government administration carried out by officials beyond their authority. The concept of abuse of authority has two legal regimes, namely administrative law and criminal law. The two regimes have a tangent point to each other. As in the case of mining business permits (IUP), the authority to issue permits attached to the office is related to government administrative law, but when there are violations of authority that are contrary to general principles, it can immediately turn into a criminal act of corruption related to legal aspects. criminal.